Analysis of the Juridical Protection of the Most Traditional Health Laws in the Perspective of the Law of the Republic of Indonesia Number 36 of 2009 Concerning Health - Razy, Fakhruddin; Ariani , Malisa (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Abstract: In accordance with the ideals of the Indonesian people as referred to in Pancasila and the Preamble of the 1945 Constitution of the Republic of Indonesia that health is a human right and one of the elements of welfare that the state must realize. The government as the holder of the highest power has the authority to achieve the highest possible health status for the community by carrying out comprehensive integrated health efforts. The results showed that Law Number 36 Year 2009 concerning Health has not fully provided legal protection for traditional health service business actors, namely traditional health workers and for traditional health service consumers, namely patients / clients. The hope is that the government should does special legislation regulating traditional health services specifically because traditional health services are currently increasingly diverse in treatment techniques and the more trusted by the Indonesian people.